2014
DOI: 10.3906/vet-1404-76
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, cellular, and physiological determinants of bull fertility

Abstract: Bull fertility, defined as the ability of the spermatozoon to fertilize and activate the ovum and then support embryonic and even fetal development, is a crucial factor influencing animal reproduction and production efficiency. Despite significant influences of fertility on herd genetic improvement and efficient cattle production, the mechanisms regulating this phenotype and reliable biomarkers associated with bull fertility are poorly defined. Specifically, there is a broad lack of knowledge in bull fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Reproduction efficiency of the male is one of the most important factors influencing sustainability of livestock as cryopreserved sperm from the elite bulls are widely distributed around the world by means of artificial insemination 1 . Male fertility is defined as the ability of sperm to fertilize the egg and sustain embryo development 2 and accurate prediction of dairy bull fertility is still a significant challenge despite of the advances in genetic selection of dairy herds 1 . As well established, herd fertility is determined by female performance but aspects of male physiology are also important, as the AI industry still faces challenges related to bull subfertility 1 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Reproduction efficiency of the male is one of the most important factors influencing sustainability of livestock as cryopreserved sperm from the elite bulls are widely distributed around the world by means of artificial insemination 1 . Male fertility is defined as the ability of sperm to fertilize the egg and sustain embryo development 2 and accurate prediction of dairy bull fertility is still a significant challenge despite of the advances in genetic selection of dairy herds 1 . As well established, herd fertility is determined by female performance but aspects of male physiology are also important, as the AI industry still faces challenges related to bull subfertility 1 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The most accurate method for testing the bull fertility is insemination of many fertile females (Amann, 2005), but this method is time-consuming, expensive Sperm viability, reactive oxygen species, and DNA fragmentation index combined can discriminate between above-and below-average fertility bulls for routine use, and allows only a limited number of bulls to be tested at any given time. Thus, researchers and commercial AI companies continuously strive to develop alternative methods to predict bull fertility so that producers can capitalize on desired genetics to improve their herd using frozen semen (Parisi et al, 2014). Several researchers reported that sperm motility (Correa et al, 1997;Rodríguez-Martinez, 2013), velocity parameters (Januskauskas et al, 2003;Nagy et al, 2015), viability and membrane integrity (Christensen et al, 2005(Christensen et al, , 2011, morphology (Söderquist et al, 1991;Nagy et al, 2013), capacitation status (Bailey et al, 1994;Thundathil et al, 1999), acrosome reaction status (Grippo et al, 1995;Kumaresan et al, 2016), chromatin integrity (Januskauskas et al, 2003), and lipid peroxidation status (Singh et al, 2016) were related to bull fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Once ejaculated sperm are collected, the cells are examined using different methods to assess their anatomy and function (18). These (19,20). Currently, applied techniques in Turkey include traditional semen evaluation methods in rams (21,22), bulls (23), and goats (24).…”
Section: Evaluation Of Semen From Bulls Bucks and Rams Using Advanced Cellular And Molecular Technologiesmentioning
confidence: 99%